WANPRESTASI SALES DALAM PERJANJIAN RETUR BARANG KEPADA TOKO DI DESA SUNGAI RINGIN KABUPATEN SEKADAU - NAZLA AZZAHRA AULIA AMIN NIM. A1012191049 (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstractA shop is one of the businesses that always uses sales services in procuring all the goods it buys and sells, providing the basic daily necessities needed by the community. When a shop transacts with sales in ordering goods, of course it doesn't always run smoothly and problems arise. The problem is that the goods ordered by shops and sales sometimes do not match the order, whether regarding the brand, taste, quantity of goods, or whether the goods ordered are defective or damaged. In trade terms, this is called a return of goods. Return of goods is the return of a number of goods by the buyer to the seller because the goods do not match the order or are damaged. To overcome this problem, an agreement must be made between both parties that the goods can be returned if they are not as ordered and the goods ordered are defective or damaged, so that the problem is handled properly and does not harm both parties. The form of compensation is in the form of a return of money or goods and/or services that are similar or equivalent to the loss or treatment and/or providing compensation in accordance with the provisions of the applicable laws and regulations. The problem studied is: